Current Approaches on Viral Infection: Proteomics and Functional Validations - Zheng, Jie; Tan, Boon Huan; Sugrue, Richard; Tang, Kai (Frontiers in Microbiology, 2012)
Viruses could manipulate cellular machinery to ensure their continuous survival and thus become parasites of living organisms. Delineation of sophisticated host responses upon virus infection is a challenging task. It lies in identifying the repertoire of host factors actively involved in the viral infectious cycle and characterizing host responses qualitatively and quantitatively during viral pathogenesis. Mass spectrometry based proteomics could be used to efficiently study pathogen-host interactions and virus-hijacked cellular signaling pathways. Moreover, direct host and viral responses upon infection could be further investigated by activity based functional validation studies. These approaches involve drug inhibition of secretory pathway, immunofluorescence staining, dominant negative mutation of protein target, real time PCR, small interfering siRNA-mediated knockdown, and molecular cloning studies. In this way, functional validation could gain novel insights into the high-content proteomic dataset in an unbiased and comprehensive way.